Development of a new approach to resistance spot weld AW-7075 aluminum alloys for structural applications: an experimental study – Part 1 - Pedro Bamberg (Elsevier, 2021)
7000 series aluminum alloys have particularly high strength, if compared to other aluminum alloys or even to some high strength steels. Currently, this alloy is considered on the next developments of automotive structures, as an enabler of improved mechanical and safety properties, associated with weight reduction, supporting the industry to fulfill fuel economy and greenhouse gases emissions regulations. Due to the proneness to hot cracking and welding embrittlement, the joining of 7000 series sheets is limited to mechanical methods, such as self-piercing rivets.In order to provide the automotive industry with more joining methods suitable for the proposed high strength aluminum alloy, the objective of this work is to validate the resistance spot welding process of the AW-7075 alloy. The work is split in two parts: the preliminary assessment of the suitability of current welding procedures, norms and respective parameters, where the process window, weld nugget quality and electrode life-time are evaluated. Then an innovative approach is investigated, where the use of an upslope welding schedule, CuAg0.1 electrode caps, increased force and lower overall electric resistance could successfully validate the application, attending manufacturing requirements regarding welding quality, electrode life-time and process window. The resultant microstructure characteristics were analyzed with metallographic micro-sections and the phases were determined with the electron backscattered diffraction technique.